2016
DOI: 10.1124/mol.115.101808
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Noncanonical Neurotransmitter Activation: Norepinephrine as a Dopamine D2-Like Receptor Agonist

Abstract: The Gai/o-coupled dopamine D 2 -like receptor family comprises three subtypes: the D 2 receptor (D2R), with short and long isoform variants (D2SR and D2LR), D 3 receptor (D3R), and D 4 receptor (D4R), with several polymorphic variants. The common overlap of norepinephrine innervation and D 2 -like receptor expression patterns prompts the question of a possible noncanonical action by norepinephrine. In fact, previous studies have suggested that norepinephrine can functionally interact with D4R. To our knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 57 publications
12
59
0
Order By: Relevance
“…All of the characteristics of D1R ligands are in agreement with previous reports [23,24]. D2R pharmacology was also in agreement with a previous study [25], in that norepinephrine showed less potency (pEC 50 5.220.14) relative to DA (pEC 50 6.610.10) and a selective D2R antagonist eticlopride showed complete blockade of 10M DA pre-activation and high potency (pIC 50 9.470.46). Albeit narrower luminescence drug-induced ranges, furimazine showed similar potencies and efficacies (Supplementary Figure 2C & D) Supplementary data.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…All of the characteristics of D1R ligands are in agreement with previous reports [23,24]. D2R pharmacology was also in agreement with a previous study [25], in that norepinephrine showed less potency (pEC 50 5.220.14) relative to DA (pEC 50 6.610.10) and a selective D2R antagonist eticlopride showed complete blockade of 10M DA pre-activation and high potency (pIC 50 9.470.46). Albeit narrower luminescence drug-induced ranges, furimazine showed similar potencies and efficacies (Supplementary Figure 2C & D) Supplementary data.…”
Section: Resultssupporting
confidence: 92%
“…The EC 50 values were also in close agreement with reports using different methods for measuring G-protein activation and receptor engagement [2628]. Overall, for the D1R and D2R, the potencies and efficacies of tested ligands were in agreement with previous reports [23,25,29,30], indicating the utility of the assay configuration for testing pharmacology of other receptors. It also needs to be pointed out that in this study coelenterazine H, as opposed to furimazine, was mainly used to characterize the complementation assays since coelenterazine H is much more cost-effective and affords a very good dynamic range.…”
Section: Resultssupporting
confidence: 90%
“…However, those experiments were performed with synthetic DA receptor agonists. We recently reported that DA is significantly more potent at activating any D 4 receptor (D 4.2 , D 4.4 , and D 4.7 ) than D 2 receptors (D 2S or D 2L ) ( 25 ), and we are obtaining results that indicate that DA is also more potent at activating D 4 receptors (including D 4.7 ) than D 2 -D 4 receptor heteromers (in preparation). Therefore, the inability of D 4.7 receptors to heteromerize should lead to a gain of function.…”
Section: Discussionmentioning
confidence: 74%
“…D 2 ‐like receptors—which potently inhibit DAergic neurons—have similar affinity ranges for both DA and NA, with any catecholamine binding resulting in their activation and downstream signal transduction, especially in the presence of higher (i.e., micromolar) concentrations of DA and NA (Sánchez‐Soto et al . ). Indeed, existing evidence from FSCV studies strongly suggested the possibility of cross‐activation of D 2 R as a potential mechanism mediating the inhibitory effects of high concentrations of NA in the VTA (Park et al .…”
Section: Discussionmentioning
confidence: 97%